The ANALISIS EFISIENSI BAHAN BAKAR DAN EMISI GAS BUANG PADA MOTOR YAMAHA MX KING 150: - - sandi kurniawan (IKIP PGRI KALIMANTAN TIMUR, 2026)
Motorcycle users, especially sports bikes like the Yamaha MX King 150, are often faced with the dilemma of choosing Pertalite (RON 90) or Pertamax (RON 92). The significant price difference makes many users prefer Pertalite, even though there is no certainty regarding its impact on fuel efficiency and exhaust emissions. This study was conducted to answer this problem through direct testing that measures the effect of both types of fuel on fuel consumption and emission levels. This study uses a quantitative approach with a quasi-experimental method and a One Group Pretest-Posttest Design. One Yamaha MX King 150 motorcycle was tested sequentially using Pertalite and Pertamax. The test was carried out in two stages: measuring fuel consumption efficiency in the field using the distance traveled per liter (km/l) method, and testing exhaust emissions in the laboratory using a gas analyzer to measure CO, HC, CO₂, and NOx levels. The results showed that the use of Pertamax produced higher fuel efficiency than Pertalite. Furthermore, Pertamax produces lower CO and HC emissions, indicating a more complete combustion process. These results demonstrate that despite Pertamax's higher price, this fuel offers long-term benefits in terms of both operational efficiency and environmental impact. These findings are expected to inform the public's choice of fuel and provide input to relevant parties in formulating sustainable energy policies.